Technological Surveillance on Social Insertion Strategies Aimed at the Female Prison Population (LACCEI, 2024)
This article presents the application of technological intelligence tools such as technological surveillance TS, to analyze existing social insertion strategies in the female prison population. The purpose is to offer interested parties a bibliometric analysis through the biblioshiny interface, as a tool for quantitative research in scientometric and bibliometric studies levels of analysis (sources, authors, and documents) and structural analysis (conceptual, intellectual and social). The database used for the search is science Direct, where a temporal filter was applied to obtain studies published between 2015 and 2022. The analysis results manage to identify the most relevant, emerging, and declining strategies, according to the selected data search.